2013
DOI: 10.1002/rcm.6584
|View full text |Cite
|
Sign up to set email alerts
|

In situ13CO2 pulse‐labeling in a temperate heathland – development of a mobile multi‐plot field setup

Abstract: A mobile flow-through system suitable for continuous in situ (13)CO2 pulse-labeling was successfully developed that is easily applicable in remote natural ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(161 reference statements)
0
7
0
Order By: Relevance
“…The three-factorial treatment combination of warming, drought and elevated CO2 is not expected to cause significant changes of the SOM pools after eight treatment years. Previous shorter term experiments at the specific site showed that the stimulating effects of elevated CO2 and warming on plant biomass, SOM turnover (measured via soil and leaf litter incubation bags after 1 year) and soil fauna cancelled out or were 5 reduced when combined with drought (Andresen et al 2010;Kongstad et al 2012;Larsen et al 2011;Maraldo et al 2010;Reinsch & Ambus 2013).…”
mentioning
confidence: 91%
“…The three-factorial treatment combination of warming, drought and elevated CO2 is not expected to cause significant changes of the SOM pools after eight treatment years. Previous shorter term experiments at the specific site showed that the stimulating effects of elevated CO2 and warming on plant biomass, SOM turnover (measured via soil and leaf litter incubation bags after 1 year) and soil fauna cancelled out or were 5 reduced when combined with drought (Andresen et al 2010;Kongstad et al 2012;Larsen et al 2011;Maraldo et al 2010;Reinsch & Ambus 2013).…”
mentioning
confidence: 91%
“…Unfortunately, this cannot be achieved due to the limitations of the used IRMS. Reinsch and Ambus adjusted resistor settings of the mass spectrometer to obtain higher measurement precision, but still they found that x ( 13 C) values measured by IRMS for 13 C-enriched samples ( x ( 13 C) = 50%) were also significantly dependent on CO 2 concentrations . They subsequently used an empirical relationship to correct data but the measured x ( 13 C) values never showed the expected values.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have also shown that this flux might be affected by a range of factors such as the seasonality of plant activity. Usually, more carbon is allocated below‐ground towards the end of the growing season (Balasooriya et al., ; Högberg et al., ), under exposure to elevated atmospheric CO 2 concentrations (Jin & Evans, ; Reinsch & Ambus, ), under drought conditions (Fuchslueger, Bahn, Fritz, Hasibeder, & Richter, ) or in plants grown on fertile soils (Denef, Roobroeck, Manimel Wadu, Lootens, & Boeckx, ).…”
Section: Methods Using In‐situ 13c Labelling To Study Rhizodepositionmentioning
confidence: 99%
“…Therefore, a mobile flow-through system suitable for continuous 13 C-CO 2 delivery was developed (Box 3): A gas-tight vinyl balloon (c. 3 m diameter) was filled with CO 2 free synthetic air and mixed with 13 C-CO 2 (50 or 99 atom%) that supplied the transparent chambers enclosing the vegetation of interest with air over the duration of the experiments, ranging from 4 to 7.5 hr. Air was pumped continuously through gas tight tubing via electric diaphragm pumps (Reinsch & Ambus, 2013). The first experiment was conducted at the end of the growing season (October 2010), when we observed the highest allocation of carbon below-ground as measured by 13 C in soil respiration (Reinsch et al, 2014).…”
Section: C-co 2 Pulse Labellingmentioning
confidence: 99%
See 1 more Smart Citation